PEMERTAHANAN BAHASA SUNDA DI PAGUYUBAN PASUNDAN KOTA BENGKULU - Ronaldo Ronaldo; Hasmi Suyuthi; Reni Kusmiarti (Prakata: Jurnal Bahasa dan Sastra Indonesia Serta Pembelajaran, 2025)
The problem in this study is how the preservation of Sundanese language is reviewed from the family realm in Paguyuban Pasundan, Bengkulu City and what are the efforts to preserve Sundanese language in Paguyuban Pasundan, Bengkulu City. The purpose of this study is: to describe the preservation of Sundanese language reviewed from the family realm in Paguyuban Pasundan, Bengkulu City and to describe the efforts to preserve Sundanese language in Paguyuban Pasundan, Bengkulu City. The benefits of the research are divided into three, namely the benefits for researchers, namely the results of this study are expected to be a vehicle and enrich knowledge about language maintenance, especially Sundanese in the Paguyuban Pasundan, Bengkulu City, the benefits for the community, especially Sundanese people in the Paguyuban Pasundan, Bengkulu City, this research is expected to provide a contribution as an appreciation of cultural preservation, and for the local government, this research is expected to be used as input to mutually support the culture of immigrant communities in maintaining their culture. The data in this study are in the form of conversations between members of the Paguyuban Pasundan, Bengkulu City in the family realm and data from interviews with family members in the Paguyuban Pasundan, Bengkulu City. The data collection techniques for this study are note-taking techniques, recording techniques, listening techniques, observation, and interviews. The results of this study are that in the family realm in the Paguyuban Pasundan, Bengkulu City, they still maintain Sundanese even though they have lived in Bengkulu City for a long time, by trying to use Sundanese in everyday language.